Silver Nanoparticles for the Therapy of Tuberculosis - Tăbăran AF; Matea CT; Mocan T; Tăbăran A; Mihaiu M; Iancu C; Mocan L (International Journal of Nanomedicine, 2020)
Alexandru-Flaviu Tăbăran,1,2,* Cristian Tudor Matea,2,* Teodora Mocan,2,3,* Alexandra Tăbăran,4,* Marian Mihaiu,4,* Cornel Iancu,2,5,* Lucian Mocan2,3,* 1Department of Pathology, University of Agricultural Sciences and Veterinary Medicine, Cluj-Napoca, Romania; 2Department of Nanomedicine, Regional Institute of Gastroenterology and Hepatology, Cluj-Napoca, Romania; 3Department of Physiology, University of Medicine and Pharmacy, Cluj-Napoca, Romania; 4Department of Public Health and Food Hygiene, University of Agricultural Sciences and Veterinary Medicine, Cluj-Napoca, Romania; 5Third Surgery Department, University of Medicine and Pharmacy, Cluj-Napoca, Romania*These authors contributed equally to this workCorrespondence: Teodora MocanDepartment of Physiology, University of Medicine and Pharmacy Cluj-Napoca, Romania 1 Clinicilor Street, Cluj-Napoca 40006, RomaniaTel +40 264 598575Fax +40 264 599814Email Teodora.mocan@umfcluj.roAbstract: Rapid emergence of aggressive, multidrug-resistant Mycobacteria strain represents the main cause of the current antimycobacterial-drug crisis and status of tuberculosis (TB) as a major global health problem. The relatively low-output of newly approved antibiotics contributes to the current orientation of research towards alternative antibacterial molecules such as advanced materials. Nanotechnology and nanoparticle research offers several exciting new-concepts and strategies which may prove to be valuable tools in improving the TB therapy. A new paradigm in antituberculous therapy using silver nanoparticles has the potential to overcome the medical limitations imposed in TB treatment by the drug resistance which is commonly reported for most of the current organic antibiotics. There is no doubt that AgNPs are promising future therapeutics for the medication of mycobacterial-induced diseases but the viability of this complementary strategy depends on overcoming several critical therapeutic issues as, poor delivery, variable intramacrophagic antimycobacterial efficiency, and residual toxicity. In this paper, we provide an overview of the pathology of mycobacterial-induced diseases, andhighlight the advantages and limitations of silver nanoparticles (AgNPs) in TB treatment.Keywords: nanoparticles, antimycobacterial, Mycobacterium, tuberculosis, macrophage, granuloma